Peranan Hakim Pengawas dan Pengamat dalam Pembinaan Narapidana - Putri Sarah; Herry Liyus; Tri Imam Munandar (Fakultas Hukum, Universitas Jambi, 2021)
This study aims to understand and determine the implementation of the duties of supervisory judges and observers in fostering female prisoners in Class II B Women's Prison in Jambi. To understand and know the supervisor and observer judges in the development of female prisoners in Class II B Women's Prison in Jambi. The results obtained in this study show that the implementation of the duties of supervisory judges and observers in fostering female prisoners at Class II B Women's Prison in Jambi is to ensure that judges' decisions are carried out according to law. The contribution of supervisory judges and observers in fostering female prisoners at the Class II B Women's Prison in Jambi ensures that the rights of female prisoners are protected in accordance with Article 14 of the Correctional Law. Â ABSTRAK Penelitian ini bertujuan untuk memahami dan mengetahui pelaksanaan tugas hakim pengawas dan pengamat dalam pembinaan narapidana wanita di Lapas Perempuan Kelas II B Jambi. Untuk memahami dan mengetahui hakim pengawas dan pengamat dalam pembinaan narapidana wanita di Lapas Perempuan Kelas II B Jambi. Hasil Penelitian yang diperoleh dalam penelitian ini bahwa pelaksanaan tugas hakim pengawas dan pengamat dalam pembinaan narapidana wanita di Lapas Perempuan Kelas II B Jambi yakni memastikan putusan hakim dilaksanakan sesuai undang-undang. Adapun kontribusi hakim pengawas dan pengamat dalam pembinaan narapidana wanita di Lapas Perempuan Kelas II B Jambi memastikan hak-hak narapidana wanita terlindungi sesuai pasal 14 UU Pemasyarakatan.